2021
DOI: 10.1093/nar/gkab714
|View full text |Cite
|
Sign up to set email alerts
|

m6A-express: uncovering complex and condition-specific m6A regulation of gene expression

Abstract: N 6 -methyladenosine (m 6 A) is the most abundant form of mRNA modification and controls many aspects of RNA metabolism including gene expression. However, the mechanisms by which m 6 A regulates cell- and condition-specific gene expression are still poorly understood, partly due to a lack of tools capable of identifying m 6 A sites that regulate gene expression under different conditions. Here we develop m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 112 publications
1
24
0
1
Order By: Relevance
“…Recently, the role of m6A modification abnormalities in diseases has gradually attracted people’s attention. The m6A modification refered to methylation of the N6 position of adenosine base ( Zhang et al, 2021 ), which can regulate the structure, stability, splicing, export, transcription and decay of mRNA, miRNA and lncRNA through methyltransferases, demethylases and m6A binding proteins, and then widely affect the life processes of various organisms ( Tian et al, 2020 ; Song et al, 2021 ). KIAA1429 is a major m6A methyltransferase and the largest protein of the methyltransferase complex ( Yue et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of m6A modification abnormalities in diseases has gradually attracted people’s attention. The m6A modification refered to methylation of the N6 position of adenosine base ( Zhang et al, 2021 ), which can regulate the structure, stability, splicing, export, transcription and decay of mRNA, miRNA and lncRNA through methyltransferases, demethylases and m6A binding proteins, and then widely affect the life processes of various organisms ( Tian et al, 2020 ; Song et al, 2021 ). KIAA1429 is a major m6A methyltransferase and the largest protein of the methyltransferase complex ( Yue et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the m 6 A modification level exhibited a particular decline in colon tissues of old mice. Zhang et al had previously uncovered a unique m 6 A-regulation-expression pattern in the human brain and intestine tissues and confirmed m 6 A modification and enrichment to be organ-specific processes [ 48 ]. Similarly, as m 6 A regulators, the altered expression of METTL3 and METTL14 has been observed in various diseases and age-related processes where METTL3/14 was observed as progressively and notably declined in human F2S fibroblasts undergoing replicative senescence [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALKBH5/IGF2BP1-mediated m6A modi cation contributed to SH3BP5-AS1 overexpression m6A modi cation has been con rmed to be involved in the regulation of RNA expression [13] . m6A modi cations are placed and removed by methylases and demethylases, respectively.…”
Section: Sh3bp5-as1 Promotes Pancreatic Cancer Cell Resistance To Gem...mentioning
confidence: 99%